The Importance of English in Responding to Globalization and Pursuing International Opportunities: Strengthening Students’ and Santri’s Motivation through a Seminar at IAI Nurul Hakim, West Lombok - Deki Zulkarnaen; Lila Alwyah; Noni Antika Khaerunnisa; Anggi Aprizal (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Globalization has transformed education, communication, and employment sectors, demanding young generations to possess global competencies, particularly English proficiency. Nevertheless, many students and santri still perceive English merely as an academic subject rather than a strategic instrument for accessing broader educational and professional opportunities. This community service activity aimed to enhance the awareness, understanding, and motivation of students and santri regarding the importance of English in facing globalization and achieving international aspirations such as scholarships, overseas education, global networking, and career development. The activity was conducted through an educational seminar within the Institutional Internationalization program organized by Institut Agama Islam (IAI) Nurul Hakim, Lombok Barat, involving approximately 50 participants consisting of university students and santri. The implementation employed interactive lectures, discussions, experience sharing, and question-and-answer sessions. The materials emphasized the urgency of English in the global era, opportunities for international education, personal academic experiences, and practical strategies for improving English competence among young learners. The results demonstrated increased enthusiasm, awareness, and motivation among participants regarding the strategic role of English proficiency in responding to global challenges and pursuing future opportunities. Participants showed strong interest in scholarship opportunities, international education, and personal development through English language mastery. This activity indicates that educational seminars can serve as an effective approach to strengthening global awareness and fostering an international mindset among students and santri.